2017
DOI: 10.1109/tpel.2017.2648119
|View full text |Cite
|
Sign up to set email alerts
|

Bifurcation and Large-Signal Stability Analysis of Three-Phase Voltage Source Converter Under Grid Voltage Dips

Abstract: Three-phase voltage-source converters (VSCs) are commonly used as power flow interface in AC/DC hybrid power systems. The AC power grid suffers from unpredictable shortcircuit faults and power flow fluctuations, causing undesirable grid voltage dips. The voltage dips may last for a short time or a long duration, and vary the working conditions of VSCs. Due to their nonlinear characteristics, VSCs may enter abnormal operating mode in response to voltage dips. In this paper, the transient response of three-phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(54 citation statements)
references
References 40 publications
2
52
0
Order By: Relevance
“…By applying Lyapunov-based methods, it is possible to control the PE-based unit independent of the system parameters in addition to handling large-signal disturbances [35]. In [36], the Lyapunov-based stability analysis is applied on a reduced-order model of the system in order to assess the large-signal stability of the system. Results are compared with the full-order eigenvalue-based stability analysis, and it is shown that the energy function can appropriately determine the stability boundaries of the system.…”
Section: Computation Complexitymentioning
confidence: 99%
“…By applying Lyapunov-based methods, it is possible to control the PE-based unit independent of the system parameters in addition to handling large-signal disturbances [35]. In [36], the Lyapunov-based stability analysis is applied on a reduced-order model of the system in order to assess the large-signal stability of the system. Results are compared with the full-order eigenvalue-based stability analysis, and it is shown that the energy function can appropriately determine the stability boundaries of the system.…”
Section: Computation Complexitymentioning
confidence: 99%
“…The switching details of power electronic inverters are included in these models, which leads to a large computation burden. Furthermore, the switching models are discontinuous and thus difficult to be used for small-signal [6][7][8]and large-signal analyses [9]. Therefore, instead of the switching model, the dynamic average models are usually utilized for the numerical simulation and stability analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The first step for stability analysis such as small-signal analysis and Lyapunov method [9] is to calculate a fixed equilibrium of dynamic model, followed by the linearization or calculation of energy function on the obtained equilibrium. Under balanced assumption, dynamic average model is transformed from the abc-frame into the synchronous rotating dq reference frame to obtain the fixed equilibrium [7][8][9][10]. However, the unbalanced operation of MG will produce an oscillating equilibrium and second harmonics of the state variables on dq reference frame.…”
Section: Introductionmentioning
confidence: 99%
“…This also causes a transient state of the DC distribution voltage, which refers to a fluctuation of the DC link voltage of the AC/DC converter. Also, DC-link voltage can be changed by AC voltage and current dips [17][18][19][20][21]. A robust DC voltage control characteristic of AC/DC PCS is required to supply power to the sensitive load (to voltage fluctuation) that is connected to the DC distribution in a stable manner.…”
Section: Introductionmentioning
confidence: 99%